Subjective persuasion knowledge on user engagement and the role of pathos and logos on IT media literacy by tech millennials - Kim, Jea-Young (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: IT media is a medium that represents the values of millennials, and advertising strategies must be guided by this fact.